Model human clonal hematopoiesis : using the CRISPR/Cas9 system - Lo, Yi-Hsuan (2019)
Hematopoietic malignancies are genetically complex diseases in which the serial acquisition of somatic mutations results in clonal diversity of hematopoietic stem and progenitor cells (HSPCs). This progressive event where clonal expansion and selection involved in clonal dynamics of HSPCs is called clonal hematopoiesis of indeterminate potential (CHIP). CHIP increases with age and can be found in 10% of the elderly. CHIP is associated with an increased risk to develop myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). In this study, we used CRISPR/Cas9 genome engineering in cell lines and primary human cells to introduce somatic mutations in the driver genes STAG2 and TP53 with the final goal to generate in vitro models of clonal hematopoiesis in primary adult CD34+ human HSPCs. We will use these models to further evaluate the underlying mechanism of clonal hematopoiesis and potential transformation into hematological malignancies related to dysregulation of the cell cycle, increased genomic alterations and chromosomal instability.